2021
DOI: 10.3389/fmed.2021.650381
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Guided Transthoracic Needle Biopsy: Predictors for Diagnostic Failure and Tissue Adequacy for Molecular Testing

Abstract: Background: Adequate and representative tissue from lung tumor is important in the era of precision medicine. The aim of this study is to identify detailed procedure-related variables and factors influencing diagnostic success and tissue adequacy for molecular testing in CT-guided TTNB.Methods: Consecutive patients undergoing CT-guided TTNB were retrospectively enrolled between January 2013 and May 2020. Multivariate analysis was performed for predictors for diagnostic accuracy and tissue adequacy for molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(36 reference statements)
0
5
0
4
Order By: Relevance
“…However, we did not nd any risk factors which were associated with diagnostic failure. In past investigations regarding CTguided CNB, the risk factors of diagnostic failure usually encompassed less sample tissues and larger lesion size [9,12,21,22]. In this study, we used the co-axial technique and obtained 3-4 samples from each LN, therefore, the number of sample tissues did not interfere the diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not nd any risk factors which were associated with diagnostic failure. In past investigations regarding CTguided CNB, the risk factors of diagnostic failure usually encompassed less sample tissues and larger lesion size [9,12,21,22]. In this study, we used the co-axial technique and obtained 3-4 samples from each LN, therefore, the number of sample tissues did not interfere the diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Core Biopsy due to a larger needle. 18,19 This study included 42 samples. From all the samples, the majority gender is male, 30 patients (71.4%).…”
Section: Discussionmentioning
confidence: 99%
“…26 Moreover, in the age of precision medicine, core biopsies allow for the characterization of tumor genomics which plays an increasingly important role in patient management. A recent study has shown that obtaining more than two core samples, and submitting samples in two cassettes improved tissue adequacy for molecular testing, 27 the latter of which is part of our routine practice.…”
Section: Patient Selectionmentioning
confidence: 99%